Penerapan Strategi Gastrodiplomasi Pemasaran Produk dan Acara Makanan Peru di Indonesia Pada Tahun 2017-2021 - Al Bustomi, Abu Yazid (Global and Policy Journal of International Relations, 2023)
Abstract Peru initiate its gastrodiplomacy campaign in 2008 under the name “Cocina Peruana Para El Mundo” using Peruvian culinary culture as an instrument of diplomacy. This gastodiplomacy campaign aims to improve Peru's nation branding and also change the image of Peru. Then after several years of carrying out its gastrodiplomacy campaign, Peru became a favorite foreign tourist country. Then in 2017 Peru started its gastrodiplomacy campaign in Indonesia. In carrying out its gastrodiplomacy, Peru employs various gastrodiplomacy strategies. This research will identify two gastrodiplomatic strategies of the Peruvian government in Indonesia in 2017-2021. The method used in this research is descriptive research method. The data collected by this research is secondary data obtained through literature study. The analysis technique used in this research is qualitative. The formulation of the problem that will be answered in this research is how is the implementation of Peru's two gastrodiplomacy strategies in Indonesia in 2017-2021? In answering the formulation of the problem, the researcher will use the gastrodiplomacy concept put forward by Paul S. Rockower and the gastrodiplomacy strategy from Juyan Zhang. The result of this research is that Peru has succeeded in implementing and carrying out two gastrodiplomacy strategies to introduce and promote Peruvian culinary culture to people in Indonesia. Keywords: Gastrodiplomacy, “Cocina Peruana Para El Mundo”, Peru, Indonesia Peru meresmikan kampanye gastrodiploamsinya pada tahun 2008 dengan nama “Cocina Peruana Para El Mundo” dengan menggunakan budaya kuliner Peru sebagai instrumen diplomasinya. Kampanye gastodiplomasi ini bertujuan untuk meningkatkan nation branding Peru dan juga merubah citra negara Peru. Kemudian setelah beberapa tahun melakukan kampanye gastrodiplomasinya, Peru menjadi negara wisatawan asing favorit. Kemudian pada tahun 2017 Peru memulai kampanye gastrodiplomasinya di Indonesia. Dalam melaksanakan gastrodiplomasinya, Peru melakukan berbagai strategi gastrodiplomasi. Penelitian ini akan mengidentifikasi dua strategi gastrodiplomasi pemerintah Peru di Indonesia pada tahun 2017-2021. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif. Data yang dikumpulkan penelitian ini adalah data skunder yang diperoleh melalui studi ustaka. Teknik analisis yang digunakan dalam penelitian ini adalah kualitatif. Rumusan masalah yang akan dijawab dalam penelitian ini adalah bagaimanakah pelaksanaan dua strategi gastrodiplomasi Peru di Indonesia pada tahun 2017-2021? Dalam menjawab rumusan masalah tersebut, peneliti akan menggunakan konsep gastrodiplomasi yang dikemukakan oleh Paul S. Rockower dan strategi gastrodiplomasi dari Juyan Zhang. Hasil dari penelitian ini adalah, Peru berhasil menerapkan dan melakukan dua strategi gastrodiplomasi untuk memperkenalkan dan mempromosikan budaya kuliner Peru kepada masyarakat di Indonesia. Kata Kunci: Gastrodiplomasi, “Cocina Peruana Para El Mundo”, Peru, IndonesiaDOI : https://doi.org/10.33005/jgp.v11i01.3865